В метре друг от друга - Липпинкотт Рейчел (Young Adult, 2020)
Экземпляры: Чит. зал (20211210) / Инвентарный номер: 48874 / Цена: 433.00 / Сис.шифр: 84(4/8) / Авт.знак: Л 61 / ГРНТИ: 17.82.31 / ББК: 84(7Амер)-44